Developmental expression of the novel voltage-gated sodium channel auxiliary subunit β3, in rat CNS - Shah, B S (Blackwell Science Inc, 2001)
1. We have compared the mRNA distribution of sodium channel alpha subunits known to be expressed during development with the known auxiliary subunits Naβ1.1 and Naβ2.1 and the novel, recently cloned subunit, β3. 2. In situ hybridisation studies demonstrated high levels of Nav1.2, Nav1.3, Nav1.6 and β3 mRNA at embryonic stages whilst Naβ1.1 and Naβ2.1 mRNA was absent throughout this period. 3. Naβ1.1 and Naβ2.1 expression occurred after postnatal day 3 (P3), increasing steadily in most brain regions until adulthood. β3 expression differentially decreased after P3 in certain areas but remained high in the hippocampus and striatum. 4. Emulsion-dipped slides showed co-localisation of β3 with Nav1.3 mRNA in areas of the CNS suggesting that these subunits may be capable of functional interaction. 5. Co-expression in Xenopus oocytes revealed that β3 could modify the properties of Nav1.3; β3 changed the equilibrium of Nav1.3 between the fast and slow gating modes and caused a negative shift in the voltage dependence of activation and inactivation. 6. In conclusion, β3 is shown to be the predominant β subunit expressed during development and is capable of modulating the kinetic properties of the embryonic Nav1.3 subunit. These findings provide new information regarding the nature and properties of voltage-gated sodium channels during development.